Towards a More Diverse INCOSE. Issue 3 (12th November 2019) - Harding, Alan; Pickard, Andy
ABSTRACT: We often talk about the lack of women in the engineering workforce, and more broadly the need for diversity and inclusion (D&I) in our enterprises. Within INCOSE, the Empowering Women Leaders in Systems Engineering (EWLSE) initiative advocates both for women as leaders in systems engineering and for improved understanding and responses to the wider diversity issues. Let us assume that INCOSE is not as diverse as we would hope in an ideal world. Let us agree that evidence‐based decisions on how to evolve INCOSE towards that idea are desirable. This paper will establish an understanding of INCOSE's current diversity based on available data, and in doing so will answer the following questions: 1) Why is it important for INCOSE to be diverse? 2) What do we mean by diversity with respect to INCOSE? 3) What do we know about INCOSE diversity today, and how does it compare to equivalent societies and the wider communities in which we operate? 4) Where are the gaps and what can we do to improve INCOSE diversity?